Stage-III and -IV endometrial cancer: A single oncology centre review of 104 cases. (2nd January 2016) - Solmaz, U.; Mat, E.; Dereli, M. L.; Turan, V.; Ekin, A.; Tosun, G.; Dogan, A.; Ozdemir, I. A.; Oztekin, O.; Sanci, M.
Abstract : The objective of this study was to evaluate the clinicopathological characteristics, treatment and prognosis of advanced endometrial cancer (EC). Patients who underwent surgery for advanced EC between January 1995 and December 2012 were retrospectively reviewed. Patients with missing data, concurrent cancers or uterine sarcomas and those who did not undergo surgery were excluded. The effects of clinicopathological factors on progression-free survival (PFS) and overall survival (OS) were analyzed. A total of 104 patients were included. Most presented with endometrioid histology (74%) and stage-III disease (87.5%), and 76.9% underwent optimal cytoreduction. A multivariate analysis confirmed that lymphovascular space invasion (LVSI) is an independent poor prognostic factor for PFS [odds ratio (OR): 21.37, p = 0.005] and OS [OR: 8.09, p = 0.044]. Suboptimal cytoreduction is another independent poor prognostic factor for PFS [OR: 5.68, p < 0.001]. Our study demonstrated that LVSI and optimal cytoreduction are the most significant factors affecting the survival of advanced EC patients.